A Bioenergetic Framework for Assessing Soil Organic Matter Persistence - Williams, Elizabeth K.; Plante, Alain F. (Frontiers in Earth Science, 2018)
The emerging view of soil organic matter (SOM) persistence asserts that SOM exists as a continuum of organic material, continuously processed by the decomposer community from large biopolymers to small monomers and with increasing oxidation and solubility, protected from decomposition through mineral aggregation and adsorption. Microbial community and ecosystem dynamics regulate the exchange of both nutrients and carbon between the soil and the atmosphere through the mineralization of SOM. Because these ecosystem dynamics are driven by net energy flows, analysis of SOM bioenergetics can provide complementary constraints to SOM models as well as insight into the fundamental conundrum of why thermodynamically unstable organic matter persists in soil. Microbial substrate preference has been shown to depend on the energy status of the potential substrates in terms of energy required and energy returned. Here we propose a framework for assessing the persistence of SOM utilizing thermally determined activation energy (Ea) and energy density (ED), tested on a suite of soils that have undergone alteration in field or laboratory experiments designed to isolate persistent SOM. Comparison of these energetic parameters in this framework will determine whether a chemical or physical change during SOM decomposition resulted in a change in its environmental persistence. An expanded framework of bioenergetics changes during SOM formation, decomposition, and stabilization is proposed as persistent SOM is characterized by decreased ED and Ea, relative to the bulk SOM.